Degradation of land covers in the Kharkiv region due to military actions - Kurach, Tamara; Korenets, Oleksandr; Lytvynenko, Natalia; Pidlisetska, Iryna (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
Background. The analysis of trends in land cover changes will allow to detect trends in land cover changes, which will contribute to the understanding of the reasons for changes in natural ecosystems and the development of strategies for their preservation and restoration. The analysis of land cover changes can be useful for assessing the impact of anthropogenic and natural factors on land using, which is important for making decisions about the rational using of natural resources, especially in the post-war period. The purpose of the research is to allow to detect the trends of land cover changes in Kharkiv region as a result of hostilities, using the satellite materials and statistical data from open sources. Methods. For the research, materials from remote sensing of the Earth were utilized, including methods of their processing and visualization. M a t h e m a t i c a l and statistical methods were applied to process statistical information and obtain index images resulting from the processing of satellite images and the generation of thematic raster data. The article conducts an analysis of the main trends in land cover changes in the Kharkiv region, highlighting trends for the most significantly altered land cover types, specifically forests and agricultural lands, for the period 2015-2022. Results. A general trend since 2015 has been the reduction of forested areas and agricultural lands, with a significant decrease in 2022, as a result of military actions and their consequences. Land cover degradation due to military activities is currently a prominent trend, representing the primary tendency in land cover changes. As a result of military actions in the Kharkiv region, all natural resources have suffered: lands from pollution and contamination with various types of waste, atmospheric air from emissions due to explosions and fires, water bodies, forest resources, and fauna from enemy equipment, pollution, and deliberate destruction. Conclusions. For a more detailed study of land cover changes related to military activities, especially regarding the destruction of the humus layer, soil pollution with metal fragments and explosive residues, field research and the use of high-resolution aerial or satellite imagery are necessary.